Household expenditures and wealth among young Guatemalan adults - Maluccio, John; Martorell, Reynaldo; Ramires, Luis Fernando (SAGE Publications, 2005)
In this article, we describe expenditure and wealth patterns, indicators of long-run economic well-being, for a sample of young Guatemalan adults interviewed for the Human Capital Study 2002–04, finding a number of differences across subgroups of the sample. The main difference across birth-year cohorts is that younger subjects tend to live in smaller households, with lower total annual household expenditures (and fewer durable goods), though per capita measures are similar across cohorts. This appears to be related to life-cycle fertility patterns. There is a clear positive association between parental socioeconomic status (SES) and current levels of expenditure and durable goods ownership. This association does not hold for all households, however, as there is both upward and downward “mobility” in the sample. Those living in the capital have the highest overall wealth levels, consistent with typical rural-urban patterns. Where there are expenditure differences across groups, they tend to be driven by differences in nonfood rather than food expenditures. Lastly, the study sample is relatively well off compared with their compatriots, with a poverty rate of 35% and an extreme poverty rate of only 3%, against national averages of 56% and 15%, respectively.